2019
DOI: 10.1021/acssuschemeng.9b01937
|View full text |Cite
|
Sign up to set email alerts
|

New Insight for Solid Sulfide Electrolytes LSiPSI by Using Si/P/S as the Raw Materials and I Doping

Abstract: Solid sulfide electrolyte has been researched for several years, and a high ionic conductivity has been acquired. However, it is difficult to apply in industrial manufacturing partly because the raw materials, such as SiS 2 , GeS 2 , P 2 S 5 , et al., have strict preparing conditions and are sensitive to water and oxygen in the air. Herein, we report a new method to produce solid sulfide electrolytes Li 9.54 Si 1.74 P 1.44 S 11.7 X 0.3 (LSiPSX) (X = F, Cl, Br, I), that is, using elementary substances Si, P, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…This excellent ionic conductivity could be ascribed to the 3D conduction pathway for Li + ions. Later, Bai et al [297] Recently, Li et al [299] reported that the cells formed with a core-shell material, i.e., LiNi0.8Co0.1Mn0.1O2 (NMC-811) and LiNbO3-coated LiCoO2 (LNO@LCO), and Li9.54Si1.74P1.44S11.7Cl0.3 (73:27) pressed at 280 MPa, and a 10 mm Li-In alloy foil disk pressed at 300 MPa as the cathode active materials, solid electrolyte, and anode, respectively, presented good cycling stability. They used a cathode mass loading of approximately 14.0 mg cm −2 and voltage range of 2.1-3.8 V for their experiments.…”
Section: Li7p2s8imentioning
confidence: 95%
See 1 more Smart Citation
“…This excellent ionic conductivity could be ascribed to the 3D conduction pathway for Li + ions. Later, Bai et al [297] Recently, Li et al [299] reported that the cells formed with a core-shell material, i.e., LiNi0.8Co0.1Mn0.1O2 (NMC-811) and LiNbO3-coated LiCoO2 (LNO@LCO), and Li9.54Si1.74P1.44S11.7Cl0.3 (73:27) pressed at 280 MPa, and a 10 mm Li-In alloy foil disk pressed at 300 MPa as the cathode active materials, solid electrolyte, and anode, respectively, presented good cycling stability. They used a cathode mass loading of approximately 14.0 mg cm −2 and voltage range of 2.1-3.8 V for their experiments.…”
Section: Li7p2s8imentioning
confidence: 95%
“…This excellent ionic conductivity could be ascribed to the 3D conduction pathway for Li + ions. Later, Bai et al [ 297 ] synthesized Li 9.54 Si 1.74 P 1.44 S 11.7 X 0.3 ( X = F, Cl, Br, I) and reported that the conductivity of Li 9.54 Si 1.74 P 1.44 S 11.7 I 0.3 was high as 1.35 mS cm −1 . Choi et al [ 298 ] reported studies on electronic structures of Li 9.54 Si 1.74 P 1.44 S 11.7 I 0.3 by atomic simulation.…”
Section: Sulfide Solid Electrolytesmentioning
confidence: 99%
“…The analogical Li 9.54 Si 1.74 P 1.44 S 11.7 I 0.3 recent was proved to not only have an ionic conductivity as high as 1.35 × 10 −3 S cm −1 but also possess a electrochemical window up to 9 V versus Li/Li + . [ 38 ] Therefore, the LGPS‐type electrolytes are becoming one of the most attractive solid electrolytes. To further enhance the electrochemical stability window, Li 9.42 Si 1.02 P 2.1 S 9.96 O 2.04 was synthesized by the introduction of oxygen into the LGPS‐type structure which exhibited an ionic conductivity of 3.2 × 10 −4 S cm −1 .…”
Section: Sulfide Electrolytesmentioning
confidence: 99%
“…[ 43 ] The sulfide electrolytes like Li 7 P 2.9 Mn 0.1 S 10.7 I 0.3 and Li 9.54 Si 1.74 P 1.44 S 11.7 I 0.3 exhibited a wide voltage stability up to 5 V and 9 V (vs Li/Li + ) tested by the same methods. [ 22,38 ]…”
Section: Sulfide Electrolytesmentioning
confidence: 99%
“…Initially, the electrochemical stability window of sulfides was measured by cyclic voltammetry. Early experiments demonstrated that most sulfide electrolytes possess a remarkable electrochemical stability window up to 5 V vs. Li metal [27,75,101,102] . For instance, the electrochemical window of Li 6 PS 5 X (X = Cl, Br or I) argyrodites was characterized by Boulineau et al [27] with a Li/BM-Li 6 PS 5 X/stainless steel cell.…”
Section: Electrochemical Stability Windowmentioning
confidence: 99%